Pedagogia de projetos: uma análise a partir de processos formativos no contexto da 3ª série do Ensino Médio. - SILVA, João Carlos da (2020)
This research is part of the Graduate Program in Education, from the University of Oeste Paulista (Unoeste), within the scope of Line 1: Public Policies in Education, training processes and diversity. The schools of the Social Service of Industry of the State of São Paulo (SESI-SP) implemented in their curriculum, in 2017, Integrating Axes as an interdisciplinary strategy of one or more areas of knowledge, through which students started to have the opportunity to know, integrate and apply knowledge, through thematic projects. In addition to this educational institution, the Education Secretariat of the State of São Paulo (SEE-SP) implemented, in 2019, the Elective Discipline, in the segments of Elementary Education, final grades, and High School. Both proposals start from the premise that, when choosing the discipline of interest, it makes their learning more meaningful, learning in the process of producing, raising doubts and researching and creating relationships, which encourage new searches, discoveries, understandings and knowledge reconstructions. Through the pedagogy of projects, autonomy, creativity, analytical capacity, synthesis and decision-making power are developed in high school students, allowing them to contextualize concepts and discover other meanings with their work, and the development of skills and competencies that will assist them in their personal life and professional activities. Given the interest in this process of implementation and consolidation of the Integrating Axes and the implementation of Elective Disciplines, this research aimed to analyze how the development of Project Pedagogy, present in the Integrating Axes in SESI-SP schools and in Elective Disciplines in the schools of the SEE-SP Comprehensive Education Program, it contributes to the training processes of teachers and students. The research was developed from a qualitative approach. The researched universe comprised a school from the SESI-SP network and a school from the state network, in the interior of the State of São Paulo. Participated in the research 09 (nine) students of the 3rd grade of High School, and 07 (seven) teachers. We composed two studies, one based on documentary analysis, based on the documents that establish the implementation of the Integrating Axes at SESI-SP and the Electives at SEE-SP and the other, through reflective interviews with the research participants. The analysis was carried out from the creation of categories, resulting from the documentary analysis. An analysis of formative processes in the context of high school was structured, given the experience of Project Pedagogy in these educational policies mentioned. The analysis of the documents and material produced by the research subjects, illustrated the path taken in the formative process and pointed out the student as the subject of the teaching and learning process and the teacher as the mediator. In this way, Project Pedagogy proved to be efficient for the teachers' training process, leading them to reframe their role in the teaching and learning process, understanding the student's role as protagonist and opening space for the construction of autonomy.